2011
DOI: 10.1177/0361684311410210
|View full text |Cite
|
Sign up to set email alerts
|

A Match-and-Motivation Model of How Women Label Their Nonconsensual Sexual Experiences

Abstract: Many rape victims are unacknowledged rape victims-they report an experience meeting researchers' operational definitions of rape but do not label their experience as rape. The purpose of this study was to investigate women's decisions about whether to label their experiences as rape. Participants were 77 college women (predominantly White; mean age ¼ 19.23) who had experienced rape according to the study's operational definition.The researchers used open-ended questionnaires and interviews to explore participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 34 publications
5
83
1
3
Order By: Relevance
“…Supporting this assertion, the assaults experienced by rape victims who are unacknowledged deviate to a greater degree from this "real rape" script than those of victims who are acknowledged. Their actual assaults quite often involve no or minimal physical force by the perpetrator, few assertive resistance behaviors (e.g., shouting, physically struggling) by the victim, frequent binge drinking by the victim and assailant, and (a sizable minority) involved an assailant who was the victim's romantic partner (Cleere & Lynn, 2013;Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Littleton, Axsom, Breitkopf, & Berenson, 2006;Littleton et al, 2007;Orchowski, Untied, & Gidycz, 2013;Peterson & Muehlenhard, 2011). In addition, one study found clear rape script differences between unacknowledged and acknowledged victims; the scripts of victims who were unacknowledged contained more elements of the "real rape" script (e.g., a highly violent assault involving strangers) than those of victims who were acknowledged (Kahn et al, 1994).…”
Section: Theoretical Models Of Unacknowledged Rapementioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this assertion, the assaults experienced by rape victims who are unacknowledged deviate to a greater degree from this "real rape" script than those of victims who are acknowledged. Their actual assaults quite often involve no or minimal physical force by the perpetrator, few assertive resistance behaviors (e.g., shouting, physically struggling) by the victim, frequent binge drinking by the victim and assailant, and (a sizable minority) involved an assailant who was the victim's romantic partner (Cleere & Lynn, 2013;Kahn, Jackson, Kully, Badger, & Halvorsen, 2003;Littleton, Axsom, Breitkopf, & Berenson, 2006;Littleton et al, 2007;Orchowski, Untied, & Gidycz, 2013;Peterson & Muehlenhard, 2011). In addition, one study found clear rape script differences between unacknowledged and acknowledged victims; the scripts of victims who were unacknowledged contained more elements of the "real rape" script (e.g., a highly violent assault involving strangers) than those of victims who were acknowledged (Kahn et al, 1994).…”
Section: Theoretical Models Of Unacknowledged Rapementioning
confidence: 99%
“…In other words, the rape scripts of victims who were unacknowledged deviated to a greater extent from their actual rape experience than those of victims who were acknowledged. Peterson and Muehlenhard (2011) applied an expanded "match and motivation" framework toward understanding unacknowledged rape. They posited that two processes affect victim's acknowledgment decision.…”
Section: Theoretical Models Of Unacknowledged Rapementioning
confidence: 99%
“…Bondurant, 2001;Layman et al, 1996). Further, related research shows that victims who endorse stereotypical beliefs about rape (e.g., rape myth acceptance [RMA]; Kahn et al, 1994;Peterson & Muehlenhard, 2004) and those whose rape experiences are inconsistent with their own rape scripts (Bondurant, 2001;Littleton, Axsom, Radecki Breitkopf, & Berenson, 2006;Peterson & Muehlenhard, 2011) are less likely to acknowledge and label their own experience as rape.…”
Section: Labeling Sexual Violencementioning
confidence: 99%
“…2. See also Peterson and Muehlenhard (2011), Furthermore, it should be kept in mind that coming to terms with one's traumatic memory is a long process; sometimes it can take years for victims to label the given experience one of rape (cf. Littleton and Grills-Taquechel 2011;Artime, McCallum, and Peterson 2014;Harned 2005;Wilson and Miller 2016).…”
Section: Holding Perpetrators Accountablementioning
confidence: 99%